AN ASSESSMENT ON SOIL DISTURBANCE OF BANGKOK CLAY SAMPLES IN RELATION WITH THE INTRINSIC COMPRESSION BEHAVIOR - P. H. Giao; N. Phien-wej; H. Tanaka (International Association of Lowland Technology, 2004)
Recent reseraches have again stirred up the soil disturbance issue and clearly indicated how significantly it could affect on soil characterization, empirical relationship between different soil parameters and, d=finally, design calculations. In this study, analyses of sample quality were carried out for a large amount of the samples taken from a coastal site near the Gulf of Thailand. The results of the study on intrinsic, compression suggested that Bangkok clay seems to be less cemented than some other clays known for being strictured like Pusan or Louseville clays. By putting this finding next to the fact that Bangkok clay has not a big thickness, one can consider that the soil disturbance of Bangkok clay would not be so critical. On the other hand, the analysis have indicated that samples collected by the procedure of wash boring and Shelby sampling tube as commonly practiced in Bangkok plain were clearly subjected to soil disturbance. Consequently, quality of Bangkok clay samples to be tested should not be taken for granted as it has been for decades, and more studies on disturbance of Bnagkok clay as well as an improvement in sampling procedure are therefore needed.